Tuning the photoactivity of TiO2 nanoarchitectures doped with cerium or neodymium and application to colour removal from wastewaters. Issue 7 (21st March 2021) - Vieira, Gabriela Bonfanti; Scaratti, Gidiane; Rodembusch, Fabiano Severo; De Amorim, Suelen Maria; Peterson, Michael; Puma, Gianluca Li; Moreira, Regina De Fátima Peralta Muniz
ABSTRACT: The impact of cerium (Ce) and neodymium (Nd) rare-earth metal doping of TiO2 prepared by the hydrothermal method was investigated to tailor effective photocatalytic degradation of coloured wastewater under UV or visible illumination. The hydrothermal treatment of TiO2 decreased the pHpzc from 6.3 to 3.1–3.8 favouring the affinity for cationic water contaminants. Doping with Ce and Nd modified the crystallinity and the morphology of the photocatalysts and significantly increased the BET surface area and the adsorption capacity of cationic dyes. The photocatalytic activity under UV light irradiation decreased due to shielding of the catalyst active area by excessive amount of dye adsorbed. Conversely, the photocatalytic activity of the Ce and Nd doped TiO2 increased under visible light irradiation by 1.2 times as a result of the dye photosensitization effect. It was demonstrated that two-steps dark adsorption and photocatalytic reaction or one-step simultaneous adsorption and reaction can produce significantly different results for the photocatalytic degradation of dyes in coloured waters, the rate being controlled by the competitive adsorption of the reacting organics and the H2 O/OH − species. The reaction is driven by the radical oxygen species (ROS) formed on the catalyst surface the nature of which, differs under UV or visible light irradiation. The Ce-doped TiO2 and Nd-doped TiO2 photocatalysts with 0.5% rare-earth content were found to be efficient in the degradation of MB in aqueous solution, removing the colour and reducing the toxicity of wastewaters. GRAPHICAL ABSTRACT: UF0001